An Introduction to Javanese Gamelan Music - SURJODININGRAT, R.M. Wasisto (Gadjah Mada University Press, 1996)
It is interesting to note that according to Western scholars pelog is older than slendro, and pelog was introduced in Java and Bali by the ancestors of the present Javanese and Balinese people themselves, while slendro was introduced much later, probably as late as the 8th century by the Syailendras of Central Java. Any how, at the end of the era of the Hindu Javanese kingdoms in East Java in the late 15th century, almost all gamelaninstruments known today, with the exception of rebab, were already known.